2020
DOI: 10.1038/s41390-020-01117-7
|View full text |Cite
|
Sign up to set email alerts
|

Infants exposed to antibiotics after birth have altered recognition memory responses at one month of age

Abstract: Background: Neonatal exposure to antibiotics, in the absence of infection, results in abnormal learning and memory in animals and is linked to changes in gut microbes. The relevance of early-life antibiotic exposure to brain function in humans is not known. Methods: Recognition memory was assessed at 1 month of age in 15 term-born infants exposed to antibiotics (with negative cultures) and 57 unexposed infants using event-related potentials (ERPs). Linear regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In addition to evidence from experimental studies, a recent longitudinal population-based study reported that early-life antibiotic exposure is associated with an increased risk for psychiatric disorders [ 81 ]. Another recent clinical study also showed an altered auditory processing and recognition memory responses in infants who received intravenous antibiotics after delivery, supporting the importance of microbiota-gut-brain axis in humans during early life [ 80 ]. As a neurodevelopmental condition, autism spectrum disorder has also been linked to gut microbiota-brain axis dysfunction [ 90 ].…”
Section: Impact Of Antibiotic Use On Gut Microbiome-brain Axismentioning
confidence: 85%
See 1 more Smart Citation
“…In addition to evidence from experimental studies, a recent longitudinal population-based study reported that early-life antibiotic exposure is associated with an increased risk for psychiatric disorders [ 81 ]. Another recent clinical study also showed an altered auditory processing and recognition memory responses in infants who received intravenous antibiotics after delivery, supporting the importance of microbiota-gut-brain axis in humans during early life [ 80 ]. As a neurodevelopmental condition, autism spectrum disorder has also been linked to gut microbiota-brain axis dysfunction [ 90 ].…”
Section: Impact Of Antibiotic Use On Gut Microbiome-brain Axismentioning
confidence: 85%
“…During this critical window, morphological and functional development in CNS also takes place, which is likely to be directly or indirectly influenced by gut microbiota [ 78 , 79 ]. A growing body of evidence from both epidemiological [ 80 , 81 , 82 ] and experimental studies [ 71 , 83 , 84 ] indicates that the gut microbiota has a crucial role in modulating brain function and behavior via gut-brain axis.…”
Section: Impact Of Antibiotic Use On Gut Microbiome-brain Axismentioning
confidence: 99%
“…Moreover, multiple independent research groups studying rodents have shown that early antibiotic exposure likely has a profound, organizational impact on gene expression, brain structure and function, and behavior ( Diaz Heijtz et al., 2011 ; Guida et al., 2018 ; Leclercq et al., 2017 ; Minter et al., 2016 ; Ogawa et al., 2020 ; Schmidtner et al., 2019 ). These findings have direct translational relevance since antibiotic exposure at birth in humans has been shown to alter recognition memory in one-month-old infants, as assessed by event-related potentials ( Hickey et al., 2021 ). Taken together, existing research is provocative but incomplete, clearly indicating that additional preclinical research is necessary to determine the overall impact of early antibiotic exposure on neurodevelopment.…”
Section: Introductionmentioning
confidence: 93%
“…Studies have established that even indirect contact with a viral infection in utero can lead to adverse effects in fetuses, suggesting that the maternal immune response and symptoms of infections may contribute to adverse prenatal development 1,2 . While treatments for infection that may restore maternal health are available, such as antiviral and antibiotics, there may be negative neurodevelopmental consequences for the fetus 3,4 .…”
Section: Introductionmentioning
confidence: 99%